Reasserting the maqāṣid of Islamic Revealed Knowledge curricula: the experience of the Department of Qurʾan and Sunnah Studies at IIUM. - Jamil, Khairil Husaini (IIUM Press, 2020)
Defining the characteristics of excellence for Islamic education institutions has proven to be one of the most challenging and highly debated issues in the modern time. On the one hand, ideals and visions derived from certain philosophical presuppositions or religious outlooks are competing to mould the shape of academic programme offered by the institutions. On the other, the official authority, whose directives an institution is subjected to abide by, often projects certain standards to measure the output of excellent production, mostly in relation to industrial demands. In the case of Islamic studies programme, or as it is named in the International Islamic University Malaysia, Islamic Revealed Knowledge and Heritage, there are notions of maqāṣid being gradually discussed by its scholars and proponents of Islamic education alike. This conception of maqāṣid, which can also be called maqāṣid tarbawiyyah, seems to correspond slightly to the theory of Outcome Based Education adopted by the Malaysian Qualification Agency – a body responsible for the assurance of quality education. However, it treats the aspects of purpose and objective in light of the Islamic scriptural thought and educational philosophy. This paper shares the experience of the Department of Qurʾan and Sunnah Studies in IIUM in formulating its Programme Learning Outcome in accordance with OBE and multiple level educational agenda, i.e. global, national and university, whilst navigating through the growing discourse of maqāṣid of Qurʾān and Sunnah studies. It speaks of the thoughts and efforts conveyed by the department to advance its ethos of “traditional embracement, critical engagement, and spiritual enhancement” through its curriculum design. The paper discusses amongst others the development of discourse pertaining to maqāṣid al-Qurʾān wa al-Sunnah and key important elements of educational objectives according to the views of Muslim scholars in the field of Qurʾān, Sunnah and Sīrah Studies. It ambitiously aims as an invitation to scholars to contribute to the narratives of maqāṣid in curricula management and policy making as well as the enhancement of Islamic philosophy of quality and educational excellence.